Philosophy of Progressivism in Learning IPS Education in The Era of Society 5.0 - Falaq, Yusuf; Faza, Iqbal; Samders, Amrei (Program Studi Tadris IPS Fakultas tarbiyah IAIN Kudus, 2023)
Social studies education is a form of integration of the social sciences and humanities which aims to make students able to be independent, responsive, responsible and think critically about a social problem that occurs in their surroundings. Of-course this will have an impact on changes that make progress in society and the country. A framework that understands that social studies education is a reflection of civilized national character is needed in the midst of the Society 5.0 era which requires society to be able to control and balance artificial intelligence and social intelligence in order to solve all kinds of national problems. Society 5.0 provides an illustration that everything can be moved and connected through data, including in it as an effort to overcome social problems in society. Social studies education is very strategic because it can balance the two things. This is in accordance with the flow of progressive philosophy which emphasizes the word progress in changes that lead to a good direction. In particular, this writing has the aim of bringing more open and broader thinking about the development of the times so that it is more perceptible that an education aims to lead to better progress. This writing uses a library study method. From the results of this literature study resulted in writing the implementation of the philosophy of progressivism in social studies education.